Combining part-of-speech tagger and inflectional lexicon for Croatian - Agić, Željko; Tadić, Marko; Dovedan Han, Zdravko (2008)
This paper investigates several methods of combining output of a third-order Hidden Markov Model PoS/MSD tagger and a highcoverage inflectional lexicon for Croatian. Our primary motivation was to improve overall tagging accuracy of Croatian texts by using our newly-developed PoS/MSD tagger. We also wanted to compare its tagging results – both standalone and utilizing the morphological lexicon – to the ones previously described in (Agić, Tadić, 2006), provided by the TnT statistical tagger applied to Croatian which we used as a reference point having in mind that both implement the second-order HMM tagging procedure. At the beginning we explain the basic idea behind the experiment, its motivation and importance from the perspective of processing the Croatian language. We also describe all the tools and language resources used in the experiment, including their operating paradigms and input and output format details that were of importance. With the basics presented, we describe in theory all the possible methods of combining these resources and tools with respect to their paradigm, input and production capabilities and then put these ideas to test, using the de facto standard recall, precision and F-measure framework. Results are then discussed in detail and conclusions and future work plans are presented.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG